Prokaryotic Community Composition in Arctic Kongsfjorden and Sub-Arctic Northern Bering Sea Sediments As Revealed by 454 Pyrosequencing - Zeng, Yin-Xin; Yu, Yong; Li, Hui-Rong; Luo, Wei (Frontiers in Microbiology, 2017)
Fjords and continental shelves represent distinct marine ecosystems in the pan-arctic region. Kongsfjorden is a glacial fjord that is located on the west coast of Svalbard, and is influenced by both Atlantic and Arctic water masses. The Bering Sea consists of a huge continental shelf in the northeast and a deep ocean basin in the southwest, and is influenced by Pacific water. Microbial community compositions of Arctic sediment samples BJ4 from outer basin and BJ36 from inner basin of Kongsfjorden and sub-Arctic samples NEC5 from shallow shelf and DBS1 from deep basin region of the northern Bering Sea were investigated using 454 pyrosequencing of archaeal and bacterial 16S rRNA genes. Most archaeal sequences in the sediments were related to Thaumarchaeota, though Euryarchaeota were more abundant in the Arctic glacier-influencing inner basin sediment BJ36. Thaumarchaeota Group C3 was the dominant archaeal population in all samples. Proteobacteria and Bacteroidetes dominated the sediment bacterial communities. Acidobacteria and Actinobacteria were also dominant in the northern Bering Sea samples. Alphaproteobacteria and Epsilonproteobacteria were the two main classes in Kongsfjorden sediment bacterial communities while Deltaproteobacteria and Gammaproteobacteria were dominant in the northern Bering Sea sediments. Differences in the presence and abundance of other dominant archaeal and bacterial populations were observed among sediment samples. In contrast to archaeal community differences that the Arctic BJ36 archaeal community was distinct from the sub-Arctic sediments and the Arctic outer basin sediment BJ4, cluster analysis based on bacterial OTU (Operational Taxonomic Unit) distributions indicated that the Arctic and sub-Arctic bacterial communities segregated from one another. These results suggest that the sediment archaeal and bacterial community compositions can be driven by different environmental factors. Differences in the presence and abundance of particular archaeal species (e.g. Candidatus Nitrosopumilus and Methanococcoides) or bacterial species (e.g. Sulfurimonas, Sulfurovum and Desulfobulbaceae) involved in biogeochemical cycles were also observed among sediment samples. At the same time, despite the community variation, some phylotypes (e.g. Marinicella) were dominant in all sediments. This study indicates diverse microbial communities inhabiting pan-arctic marine sediments, and highlights potential roles for Archaea and Bacteria in global biogeochemical cycles in these environments.